HUBUNGAN RESILIENSI MATEMATIS DENGAN KEMAMPUAN PEMECAHAN MASALAH DALAM MENYELESAIKAN SOAL CERITA MATRIKS PADA SISWA SMA - Damayanti, Triya (Jurnal AlphaEuclidEdu, 2025)
Mathematics is one of the most important subjects in various fields of science, but it is often considered difficult by students, especially in matrix materials. Mathematical problem solving, using the Polya approach, is essential in understanding this topic. However, many students face obstacles, such as a lack of confidence and motivation. Mathematical resilience, which involves unyielding and self-confidence, plays a very important role in overcoming these difficulties. This study aims to determine the relationship between mathematical resilience and problem-solving ability of high school students, especially in matrix materials. Using a correlational approach, this research investigates how Class XI mathematics specialisation students at MAN 2 Pontianak relate to one another in terms of mathematical resilience and problem-solving abilities as they pertain to solving Matrix narrative issues. This research used a sample of seventy-eight students enrolled in the school's mathematics specialisation course. Both test and non-test equipment were used to gather data. The first tool is a test consisting of three questions designed to assess students' problem-solving abilities; the second tool is a questionnaire consisting of thirty items designed to assess students' mathematical resilience on a Likert scale. The Spearman correlation test is used for data analysis. An study yielded a correlation value of 0.256, suggesting a weakly positive association between mathematical resilience and problem-solving abilities.